Is there an American way of aging? Income dynamics of the elderly in the US and Germany - Thomas L. Hungerford (Levy Economics Institute of Bard College, 2002)
This study examines income dynamics during individuals' first 12 years of retirement. Two questions are asked: (1) Are the economic experiences of the elderly in the United States unique, or are they similar to those of the elderly in Germany? and (2) What is the role of Social Security in shaping these economic experiences? The results show major differences in the experiences of retired individuals as they age in the respective countries. Retired Germans generally maintain their accustomed living standards, whereas retired Americans experience a declining standard of living.
Keywords: 330